Comparação entre as colpocitologias oncóticas de mulheres infectadas e não-infectadas pelo vírus da imunodeficiência humana - Homero Caporali de Oliveira (2008)
Objectives: The aims of this study were to determine the prevalence of abnormal cervical smears in women uninfected and infected with the human immunodeficiency virus (HIV), and to compare the results according to their HIV-status. Method: Two hundred and thirty two women between the ages of 13 and 60 years were enrolled in the study: 161 were HIV-infected and 71 uninfected. Those women were excluded who refused to take part in the research, who had been submitted to histerectomy, or were pregnant. Data was collected from October 2006 to August 2007 at two different university health centres. The women were subject to anamnesis and a complete gynecological examination. The samples were collected using cytobrush and Ayre spatula. Only conventional Pap smears were performed. Final cytological diagnosis was performed by the same cytopathologist in all cases. Cervical smears were reviewed and classified according to the Bethesda System 2001. Those samples having at least ASCUS were considered abnormal. Cytological, gynecological, obstetric and socio-demographic variables were considered in the statistical analysis. Calculations were performed with R Software. Results: The prevalence of abnormal cytology was 13 (9,3%), ocurring in HIV-infected women only. HIV-infected women had more ASCUS (p=0,053) and abnormal cytology (p=0,005). Those women with a lower educational level (<7 years) (OR=2,9;p=0,001), smokers (OR=9,8;p<0,001), widows (OR=5,5;p=0,001), with higher rates of lifetime sexual partners (p=0,001), pregnancies (p=0,022) and abortions (p=0,018), as well as those using barrier contraceptive methods (OR=5,6;p<0,001), with abnormal colposcopy (OR=33,6;p<0,001), or receiving consultation for reasons of routine control (p<0,001) were more likely to be HIV-infected. ASCUS, HPV and LSIL (p<0,001) demonstrated significant differences in the abnormal cervical cytologies, when compared to the normal ones. In the final multivariable analysis, only abnormal colposcopy (OR=3,9;p=0,04) and smoking (OR=3,9;p=0,04) showed association with abnormal cytology. Conclusion: In this study it was not possible to confirm the association between HIV-infection and abnormal cytology. KeyWords: HIV-Infection; Vaginal Smears; Cervical Intraepithelial Neoplasia; Human Papillomavirus; Neoplasms, Squamous Cell.